1998
DOI: 10.1161/01.cir.98.7.628
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed Previous Infection With Chlamydia pneumoniae (TWAR) and Its Presence in Early Coronary Atherosclerosis

Abstract: Serological evidence for C pneumoniae infection frequently precedes both the earliest and more advanced lesions of coronary atherosclerosis that harbor this intracellular pathogen, suggesting a chronic infection and developmental role in coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(67 citation statements)
references
References 42 publications
4
61
0
2
Order By: Relevance
“…2,8 More recently, clinical investigations reported that seropositivity for Chlamydia pneumoniae correlates with intima-media thickness. 5,9 In the present study we surveyed the presence of Chlamydia pneumoniae in segments of LAD in young population.…”
mentioning
confidence: 99%
“…2,8 More recently, clinical investigations reported that seropositivity for Chlamydia pneumoniae correlates with intima-media thickness. 5,9 In the present study we surveyed the presence of Chlamydia pneumoniae in segments of LAD in young population.…”
mentioning
confidence: 99%
“…24 In fact, C. pneumoniae has been successfully isolated from atherosclerotic lesions 25 and, based on the laboratory and clinical evidence, pilot trials of macrolide antibiotics in both patients with coronary heart disease 26 and in an animal model 27 were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies have detected C. pneumoniae in atherosclerosis arterial tissue using two different techniques such as polymerase chain reaction (PSR) and immunohistochemistry (IHC) but results are often difficult to interpret. (Cambell et al, 1995, Davidson et al, 1998 None of these techniques nowadays is perfect to detect the C. pneumoniae infection. There are long terms studies needed if we want to determine a potential role of C. Pneumoniae infection in the start of atherosclerosis plaque or only in arteriosclerosis progression Coronary artery disease being a specific form of atherosclerosis, is a very difficult case for studying.…”
Section: Coronary Artery Diseases Et C Pneumonia Infectionmentioning
confidence: 99%